Log Monitoring System using Quick Response (QR) Code: A State University’s COVID – 19 Contact Tracing System - Paculaba, Anna Monica Cruz; S. Bathan, Mark Angelo; Niego, Erickson L. (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2022)
Contact tracing is the technique employed by public health units and the national close contact service to track down persons who may have been exposed to COVID-19 by interaction with a suspect, confirmed, or probable case during their infectious period. This study focused on the development of a Log Monitoring System Using Quick Response (QR) Code in Samar State University as an institution’s tracing system for COVID – 19 preventions. The study was designed as a tool for managing the everyday logs of the employees, students, and visitors to track down the person who is in close contact to a COVID – 19 positives. The waterfall model was used in developing the system and descriptive research design was used to determine the effectiveness of the system along with functionality, reliability, usability, efficiency, maintainability, and portability. The participants of the study were the employees, students, and visitors of SSU. Each participant has given an ISO 9126 quality standard questionnaire for the evaluation of the effectiveness of the system. The result revealed that using the system, the conduct of contact tracing of the possible COVID – 19 suspected individuals was done easily and with reliability.